Attitudes of preservice teachers towards teaching deaf and ESL students (2013)
In this document we will discuss the complexity around education for the deaf. The most important issue to consider is about the long process students have to assume when they learn English as a foreign language. All human beings acquire a mother tongue during their first few years of life; for many of the hearing impaired, the mother tongue is a sign language code that differs according to place of origin. Sign languages are significantly disparate from oral languages in that they are not produced or perceived in the same way as oral languages. This is to say, sign languages rely on visual perception, whereas oral languages depend on auditory perception. As a reflection we discuss about how effective is for deaf students to learn a language they will never speak, they will never listen and which is not communicatively useful abroad.